2016
DOI: 10.1016/j.ijcard.2016.06.097
|View full text |Cite
|
Sign up to set email alerts
|

Over-expansion capacity and stent design model: An update with contemporary DES platforms

Abstract: This update presents valuable novel insights that may be helpful for careful selection of stent size for contemporary DES based on model designs. Such information is especially critical in left main bifurcation stenosis treatment where overexpansion to larger oversized diameter may be required to ensure full stent apposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 24 publications
0
52
0
1
Order By: Relevance
“…DES from different manufactures are available with different diameter ranges, but only a few manufacturers provide large diameter stents whose nominal range falls within the typical LM size (4.5-5 mm) ( Table 2). Bench-top tests have confirmed the ability of different DES platforms with a nominal size of 3-4 mm to maintain structural integrity when expanded to higher diameters 23,24 . However, major concerns exist regarding specific expansion limits, suboptimal plaque coverage (due to reduced metal-artery ratio) and the preservation of drug-elution kinetics.…”
Section: Left Main Stent Sizingmentioning
confidence: 87%
“…DES from different manufactures are available with different diameter ranges, but only a few manufacturers provide large diameter stents whose nominal range falls within the typical LM size (4.5-5 mm) ( Table 2). Bench-top tests have confirmed the ability of different DES platforms with a nominal size of 3-4 mm to maintain structural integrity when expanded to higher diameters 23,24 . However, major concerns exist regarding specific expansion limits, suboptimal plaque coverage (due to reduced metal-artery ratio) and the preservation of drug-elution kinetics.…”
Section: Left Main Stent Sizingmentioning
confidence: 87%
“…Larger distance between struts can reduce the scaffolding, increasing the risk of plaque prolapsing and potentially reducing drug delivery efficacy. 11 Self-apposing stent presents a consistent cell geometry also at 6.0 mm. diameter without any distortion of the strut.…”
Section: Discussionmentioning
confidence: 85%
“…Overdilation could cause significant deformation with large changes in terms of cell opening and strut distortion. Larger distance between struts can reduce the scaffolding, increasing the risk of plaque prolapsing and potentially reducing drug delivery efficacy . Self‐apposing stent presents a consistent cell geometry also at 6.0 mm.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, excessive over‐expansion was observed in 74% of patients in the Control group . Over‐expanded DES are characterized by (a) important strut distortion (which may limit the anti‐proliferative effectiveness by damaging the drug coating) and (b) stent cell enlargement, which may impact the scaffolding properties . Carina reconstruction is also often suboptimal especially in the case of two‐stents techniques .…”
Section: Discussionmentioning
confidence: 99%
“…QCA analysis pre-and post-stenting are reported in Table 3 Over-expanded DES are characterized by (a) important strut distortion (which may limit the anti-proliferative effectiveness by damaging the drug coating) and (b) stent cell enlargement, which may impact the scaffolding properties. 5,26 Carina reconstruction is also often suboptimal especially in the case of two-stents techniques. 27,28 In contemporary practice, the single (MV) stent approach has become the default strategy.…”
Section: Angiographic and Ivus Analysismentioning
confidence: 99%